The peace Treaties of Karlowitz (1699) in the perspective of Austrian diplomacy - Ciobanu, Veniamin (Balcanica Posnaniensia. Acta et studia, 2003)
The author of the article analyzes the Austrian interpretation of the peace Treaties of Karlowitz (1699) through an unpublished memorandum written in Italian around 1716, intended for policymakers at the Habsburg imperial court. This document reflects the perception that the peace signed at Karlowitz did not represent a lasting settlement, but rather a temporary truce in Austro-Ottoman relations. The main objective is to examine how, in the years following the War of the Spanish Succession (1701–1714), Austrian strategists viewed a renewed offensive against the Ottoman Empire as both politically legitimate and legally justified. The analysis is based on the Italian-language memorandum preserved in Romanian archival collections (notably in Documente privitoare la istoria românilor), which provides a critical assessment of Ottoman policy and the geopolitical situation in Southeastern Europe. According to the authors of the memorandum, the Treaty of Karlowitz had been violated multiple times by the Ottomans – particularly through the construction of new fortresses (such as Bender and Hotin) and by supporting the Hungarian uprising led by Francis II Rákóczi. They also argued that the Ottoman Empire, by its militaristic and unstable nature, could not endure in times of peace, making a renewed war inevitable. Finally, the memorandum criticized the Karlowitz negotiators for neglecting the status of the Danubian Principalities (Moldavia and Wallachia) and for ignoring the Habsburgs’ historic claims inherited from the Hungarian Crown. In conclusion, the article highlights how Austrian diplomacy in the early 18th century prepared to overturn the Karlowitz settlement, invoking European public law and an assertive reading of the regional balance of power.